پەیوەندى سۆڤیەت بە مەسەلەى کوردەوە - محمد, کمال علی (Sulaimani Journal for Humanities, 2000)
This writing is a brief of the mentitoned titel during the period of Bolshavik's authority , which Led by Lenin. Befor the end of the first world war, Kurdish people optimistic with the fact that they could get their frecdom from the Osmanian capture ,which lasted for centuries. Saikes-Piko-Sazanov agreement was the reason partition of the Osmanian state and Liberation of the other people. But the hope of a Liberated Future of Kurd has been lost the incidencof Bolshavikian revolation. Relation of Soviet government with the occupied eastern nations and supporting them in order to get their rights was not coordinated with the international principles which were defending of it, but the opposite was true it was cooperated borgua regime. In this writing the political situation of Lenin government towards Kurd, are through those relations which are achieved with Mustafa Kamal government in the framewark of cooperattion's and signing agreemments.